“At the end of the day, you need to do something”: discourses on prioritization of stormwater solutions - Low, Robinson R.; Swayne, Darby P.; Magel, Caitlin L.; Israel, Jessie; Levin, Phillip S. (Frontiers in Sustainable Cities, 2023)
As urbanization continues to expand in the Puget Sound, Washington, USA region, stormwater management has wide ranging impacts to human and ecosystem health and is therefore fundamental to creating equitable and sustainable cities. This paper brings forward dominant discourses among stormwater experts in regard to which solutions should be implemented in the Puget Sound region and what outcomes would be most beneficial to this ecosystem. We used Q-methodology to investigate differences in prioritization of stormwater solutions currently being considered in the region and explore how emergent perspectives may affect decisions for stormwater management. We chose 29 stormwater solutions falling into three categories: source control, green infrastructure, and gray infrastructure, each leading to different co-benefits and environmental outcomes. The purpose of this study is to better understand which solutions lead to the most efficient and beneficial recovery of the Puget Sound ecosystem. Through centroid extraction analysis, we discovered three discourses that capture different themes, values, and beliefs held by stormwater experts. Within our 21 participants, each shared common stormwater goals: reducing the delivery of toxics to receiving waterways and reducing stormwater quantity. Even with these shared end goals, our participants disagreed on the prioritization and overall outcomes of solution types. Our findings are important to spark discussion between municipalities with differing worldviews and outcomes associated with stormwater management and to highlight multiple benefits associated with solutions and how they can be utilized to support environmental justice.